Investigating the flow behavior of dilute aloe vera biopolymer solutions in microchannel - Fiona Ling, Wang Ming; Abdulbari, Hayder A.; Kadhum, Wafaa A.; Heng, J. T. (Taylor & Francis, 2020)
The aim of the present work is to investigate the flow enhancement performance of an organic polymeric additive extracted from Aloe Vera in a specially designed microchannel simulating the real flow in the human artery. The additive rheological and flow enhancement properties were tested using a rheometer and an open-loop microfluidics flow system, respectively. The additive concentrations and solutions flow rates were the main investigated variables in the present work. The experimental results confirmed the flow enhancement effect of the new organic additive with a maximum flow enhancement up to 94% with the addition of 100 ppm of additives at 400 mbar pressure. The flow enhancement performance in heart artery-like microchannel was lower than in the straight channel due to the complexity of the design that can result in a high back pressure.